Multilevel unilateral versus bilateral pedicular percutaneous vertebroplasty for osteoporotic vertebral compression fractures - Tan, Yixuan; Liu, Jia; Li, Xiaoming; Fang, Liangqin; He, Duowen; Tan, Junming; Xu, Guohua; Zhou, Xuhui (Frontiers in Surgery, 2023)
Study Design: Retrospective study. Objective: Controversy exists over the need for unilateral versus bilateral pedicular percutaneous vertebroplasty (PVP) for patients with osteoporotic vertebral compression fractures (OVCFs). Clinical research is scarce comparing two approaches for multi-level PVP. This study aimed at evaluating the clinical and radiographic outcomes of multi-level PVP using two approaches for OVCFs. Methods: Seventy-eight patients with OVCFs undergoing multi-level PVP were enrolled including 36 patients undergoing unilateral PVP and 42 undergoing bilateral PVP. The clinical and radiological assessments including the Visual Analogue Scale (VAS), sagittal and coronal segmental Cobb, vertebral compression ratio (VCR), and vertebral sides ratio (VSR) were evaluated preoperatively and postoperatively. Results: All patients achieved a minimum 2-year follow-up. A total of 164 fractured vertebrae were enrolled. Regarding clinical efficacy, the VAS score improved in both groups after surgery, but the two groups did not differ significantly. The changes tendency in Sagittal Segmental Cobb, VSR, and VCR were similar postoperatively, and no statistically significant difference between groups. As for the Coronal Segmental Cobb angle, patients in unilateral and bilateral groups were shown to have 5.0° ± 4.0° and 2.6° ± 2.2° degrees loss of correction at a minimum 2-years follow-up duration, respectively. The loss of correction in the Coronal Segmental Cobb of unilateral group was significantly greater than that of bilateral group. Conclusion: Both multi-level unilateral and bilateral pedicular PVP achieved significant pain reduction and vertebral height restoration. Moreover, the bilateral PVP has shown advantages in stabilizing Coronal Cobb angle in patients with OVCFs.